Bibliometric analysis of ovarian cancer immune evasion research from 2015 to 2024 - Wang, Xiaodong; Xiong, Di; Cui, Songli; Duan, Bingchen; Huang, Yiping; Ding, Gouping; Tang, Yixuan; Wang, Qianqian (Frontiers in Oncology, 2026)
BackgroundOvarian cancer remains lethal and shows limited response to immunotherapy partly due to immune evasion. We mapped global research trends on ovarian cancer immune evasion during 2015–2024.MethodsWeb of Science Core Collection and Scopus were searched on 6 Oct 2025 for English articles and reviews published 1 Jan 2015–31 Dec 2024. Records were merged and deduplicated in R (bibliometrix). Productivity, collaboration, keywords, thematic clusters, and burst terms and citations were analyzed using bibliometrix, VOSviewer, and CiteSpace.ResultsA total of 496 publications from 202 sources were included, showing rapid growth (annual growth rate ~24.6%) with a marked rise after 2020. The United States and China contributed the most output, whereas international collaboration was limited (~9.7% of authors with multiple-country affiliations). Keyword co-occurrence revealed major themes in immunotherapy, tumor microenvironment remodeling, immune checkpoint regulation, resistance mechanisms, and genetic/epigenetic modulation. Emerging hotspots highlighted tumor-associated macrophages and STAT3-centered signaling as key drivers of immune suppression and therapeutic resistance.ConclusionResearch on ovarian cancer immune evasion is expanding quickly and is shifting toward actionable targets and combination strategies. Strengthening cross-country collaboration and focusing on TME- and STAT3/TAM-directed interventions may accelerate translation and improve immunotherapy outcomes.